2021
DOI: 10.3390/ijms22179454
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs Signature for Predicting Response to GLP1-RA Therapy in Type 2 Diabetic Patients: A Pilot Study

Abstract: Type 2 diabetes (T2D) represents one of the major health issues of this century. Despite the availability of an increasing number of anti-hyperglycemic drugs, a significant proportion of patients are inadequately controlled, thus highlighting the need for novel biomarkers to guide treatment selection. MicroRNAs (miRNAs) are small non-coding RNAs, proposed as useful diagnostic/prognostic markers. The aim of our study was to identify a miRNA signature occurring in responders to glucagon-like peptide 1 receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…It occurs that circulating miRNAs could also be used to predict the effects of DM2 therapy (Table 3). After 1 year of treatment with glucagon-like peptide 1 receptor agonists (GLP1-RA), patients with initially higher expression levels of eight circulating miRNAs had a better response to therapy than those with lower levels (Formichi et al 2021). In addition to the abovementioned examples, the recent results showed that circulating miRNA may be utilized to select a personalized diet model to prevent the development of DM2.…”
Section: Circulating Mirna As Potential Biomarkers For Dm2mentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs that circulating miRNAs could also be used to predict the effects of DM2 therapy (Table 3). After 1 year of treatment with glucagon-like peptide 1 receptor agonists (GLP1-RA), patients with initially higher expression levels of eight circulating miRNAs had a better response to therapy than those with lower levels (Formichi et al 2021). In addition to the abovementioned examples, the recent results showed that circulating miRNA may be utilized to select a personalized diet model to prevent the development of DM2.…”
Section: Circulating Mirna As Potential Biomarkers For Dm2mentioning
confidence: 99%
“…In the case of patients with cardiovascular diseases, initial high miR-150 along with low miR-29a, miR-28-3p, and miR-126 in subjects on a Mediterranean diet, and low initial level of miR-145 in subjects on low-fat high-complex carbohydrate diet, was associated with a higher risk of development DM2 (Jimenez-Lucena et al 2021). Therefore, the profile of circulating miRNAs may be also used to select a group of patients for a particular treatment in DM2 (Formichi et al 2021) and nutritional therapy to lower the risk of disease development (Jimenez-Lucena et al 2021).…”
Section: Circulating Mirna As Potential Biomarkers For Dm2mentioning
confidence: 99%
“…This showed that the expression of miR-126-3p correlated positively with the reduction in fasting blood glucose (%) at T12. 52 Importantly, our work showed that miR-126-3p expression correlated positively with fasting glucose reduction (%) at T12. 52 Taken together, these studies consistently report the importance of circulating miR-126-3p in T2D.…”
Section: Article In Pressmentioning
confidence: 62%
“…52 Importantly, our work showed that miR-126-3p expression correlated positively with fasting glucose reduction (%) at T12. 52 Taken together, these studies consistently report the importance of circulating miR-126-3p in T2D. Overall, circulating miR-126-3p: (1) is significantly reduced in T2D patients and inversely associated with fasting glycamia; (2) is reduced in IGT patients and predicts the occurrence of T2D; (3) is a potential biomarker for both pharmacological (metformin/sitagliptin) and dietary therapies (low-fat vs Mediterranean diet); and (4) identifies the presence of cardiovascular disease in T2D patients.…”
Section: Article In Pressmentioning
confidence: 62%
See 1 more Smart Citation